The role of utilitarian and hedonic values on users' continued usage intention in a mobile hotel booking environment. (August 2016) - Ozturk, Ahmet Bulent; Nusair, Khaldoon; Okumus, Fevzi; Hua, Nan
Abstract: This research aims to develop and test a theory-based model that empirically investigates the antecedents of consumers' continued usage behavior intentions toward mobile hotel booking (MHB) technology. The proposed model was tested via structural equation modeling (SEM) by using data collected from 396 MHB users. Among the investigated factors, utilitarian and hedonic value had significant impacts on users' continued usage intentions. Furthermore, perceived risk, subjective norm and innovativeness significantly influenced utilitarian and hedonic value; also, perceived ease of use had a significant impact on utilitarian value. This study offers important theoretical contributions, as it provides valuable information to researchers in developing and testing related theories. In addition, the study brings clear practical implications to hotel operators, online travel agencies (OTAs), and hospitality technology vendors in developing effective marketing strategies to increase the continued usage level of MHB users.